Clinical and radiographic evaluation for two crestal sinus lift techniques: osteotome versus osseodensification. a systematic review and meta-analysis - Carlos Manuel Cobo-Vázquez; Sonia García-Rodríguez; María Eugenia Colmenares-Otero; Luis Miguel Sáez-Alcaide; Jorge Cortés-Bretón-Brinkmann; Cristina Madrigal Martínez-Pereda; Cristina Meniz-Garcia (International Journal of Implant Dentistry)
Abstract Purpose Maxillary sinus floor elevation is a safe and effective surgical technique for achieving vertical bone height, performed through either a lateral or crestal approach. The latter includes both the osteotome technique and osseodensification. The aim of this systematic review was to compare the outcomes of the classic crestal sinus lift technique and the osseodensification sinus lift approach in terms of the bone gain, marginal bone loss, survival rate, follow-up time and complications. Methods This review was performed following PRISMA guidelines. An electronic search was conducted across three databases: (1) The National Library of Medicine (MEDLINE/PubMed); (2) SCOPUS; and (3) Cochrane Central Register of Controlled Trials (CENTRAL). The Newcastle–Ottawa Quality Assessment Scale and the Cochrane Collaboration tool for evaluating risk of bias. A meta-analysis for random effects was carried out for implant survival, residual bone height and bone gain. Results Thirteen studies were included, ten studies performed the osteotome (OST) approach and three performed the osseodensification (OD) approach, with a total of 519 sites treated. The residual bone height was 5.94 and 5.00 mm for OD and OST, respectively. For bone gain, similar results were found for both groups, being 3.37 mm for OD and 3.18 mm for OST. For both groups, the most used diameter and length of the implant was 4 and 10 mm, respectively, and the implant survival rates ranged from 94.1% to 100%. OST technique reflected a complication rate of 14.32%, compared to the OD technique, which showed a complication rate of 2.78%. Conclusions It can be concluded that the maxillary sinus lift by osseodesinfication approach is a safe, predictable and successful technique compared to the osteotome approach, with similar outcomes regarding bone gain which is an important parameter for implant placement.